Representasi Ketidakadilan Gender Dalam Konstruksi Pemeberitaan Media Daring tribunnews.com - Meryana Micselen Doko (Balai Pengembangan SDM dan Penelitian Komunikasi dan Informatika (BPSDMP Kominfo) Banjarmasin, 2019)
Violence against women is a very worrying phenomenon. Various treatments and forms of violence both physically and psychologically are often experienced by women. Not infrequently found, news about women adorns on online media news. But the sad thing is that there is a tendency of the media to commodify incidents of violence against women. What is highlighted is the sensation aspect, rather than the substance of the event. This can be seen from the use of language in writing news titles. As a result, example of using titles was seem sensational. Therefore, this article aims to map and uncover the representation of gender inequality in news coverage of online media “Trbunnewes.Com”. This article uses discourse analysis by Sara Mills's feminism model. Based on the results of the study, it found that online media have helped construct gender inequality in society. This can be seen from the media coverage that not only marginalizes women but can undermine the dignity of women as creatures of God. As an agent of social construction that defines reality, the online media “Tribunnews.Com” has built a false awareness in the community that various injustices relating to violence against women in society are a result of inattention and even